2012
DOI: 10.1007/s10787-012-0139-3
|View full text |Cite
|
Sign up to set email alerts
|

Garlic (Allium sativum) down-regulates the expression of angiotensin II AT1 receptor in adrenal and renal tissues of streptozotocin-induced diabetic rats

Abstract: The up-regulation of angiotensin II AT1 receptors has been implicated as a major mediator in the development of hypertension and progressive nephropathy in experimental diabetes. In spite of the documented potential of garlic treatments in ameliorating diabetic complications, the possible involvement of the angiotensin II AT1 receptor, as a central target for the anti-diabetic potential of garlic, has not been explored. Three groups of rats were studied after 8 weeks following diabetes induction: normal, strep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 56 publications
7
13
1
Order By: Relevance
“…In the kidney, the present study also revealed that STZ treatments were associated with a significant decrease in AT 2 receptor expression throughout all nephronal segments including glomeruli and proximal and distal convoluted tubules in the cortex, collecting tubules and ducts and ascending Henle's loop segments in the inner stripe of the outer medulla, as well as inner medullary collecting ducts. The observed decrease in total intrarenal expression of AT 2 receptors is in direct accordance with previous observations in the same model of experimental diabetes [17], and contrasts the documented effects of STZ treatments in upregulating intrarenal expression of AT 1 receptors [1,2,4,11,12,24,26,37]. Thus, in early diabetes, the expected decline in AT 2 -mediated mechanisms may potentiate the pathological augmentation of intrarenal AT 1 -mediated activities promoting sodium retention and hypertension, glomerulosclerosis and proteinuria, tubulo-interstitial cell hypertrophy and hyperplasia associated with stimulation of extracellular matrix production, which are the hallmark of diabetic nephropathy [2,[12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the kidney, the present study also revealed that STZ treatments were associated with a significant decrease in AT 2 receptor expression throughout all nephronal segments including glomeruli and proximal and distal convoluted tubules in the cortex, collecting tubules and ducts and ascending Henle's loop segments in the inner stripe of the outer medulla, as well as inner medullary collecting ducts. The observed decrease in total intrarenal expression of AT 2 receptors is in direct accordance with previous observations in the same model of experimental diabetes [17], and contrasts the documented effects of STZ treatments in upregulating intrarenal expression of AT 1 receptors [1,2,4,11,12,24,26,37]. Thus, in early diabetes, the expected decline in AT 2 -mediated mechanisms may potentiate the pathological augmentation of intrarenal AT 1 -mediated activities promoting sodium retention and hypertension, glomerulosclerosis and proteinuria, tubulo-interstitial cell hypertrophy and hyperplasia associated with stimulation of extracellular matrix production, which are the hallmark of diabetic nephropathy [2,[12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 91%
“…The significant reduction of AT 2 receptor expression in adrenomedullary chromaffin cells may be also implicated in a possible loss of the synergistic AT 1 /AT 2 receptor cross-talk suggested to regulate basal and stress-induced tyrosine hydroxylase transcription rates [49], and thereby leading to dysregulation of adrenomedullary catecholamine secretions. Interestingly, the up-regulatory shift in AT 2 receptor expression in the zona fasiculata/reticularis, which was also observed earlier for AT 1 receptor expression [37], has been consistently observed with either receptor type under various abnormal physiological and pathophysiological conditions including dietary sodium restriction, sodium loading, stimulated levels of aldosterone or Ang II, and water deprivation [47,[50][51][52]. Although the exact functional significance of AT 1 /AT 2 receptor perturbations in these zones is still to be elucidated, their altered expression may represent a signifi-cant adaptive factor in adrenal tissue remodeling under various pathological conditions, including early diabetes.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations